2017
DOI: 10.1002/mgg3.276
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions to stuttering: the current evidence

Abstract: Evidence for genetic factors in persistent developmental stuttering has accumulated over the past four decades, and the genes that underlie this disorder are starting to be identified. The genes identified to date, all point to deficits in intracellular trafficking in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 55 publications
0
59
0
11
Order By: Relevance
“…In addition, studies of our animal models show that astrocyte pathology persists into adulthood in these animals. Thus, human genetic findings (2), animal model studies, and independent human brain imaging studies (3,4) now all support a role for a cellular deficit in the CC in the genesis of persistent developmental stuttering.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, studies of our animal models show that astrocyte pathology persists into adulthood in these animals. Thus, human genetic findings (2), animal model studies, and independent human brain imaging studies (3,4) now all support a role for a cellular deficit in the CC in the genesis of persistent developmental stuttering.…”
Section: Discussionmentioning
confidence: 90%
“…stuttering | astrocytes | white matter | mouse vocalization | Cre-drivers S tuttering is a common neurodevelopmental disorder characterized by disruptions in the fluent flow of speech (1), typically in the absence of other neurological deficits. Stuttering displays high heritability (2), and recent studies have identified mutations in the GNPTAB, GNPTG, NAGPA, and AP4E1 genes that are associated with this disorder (3)(4)(5). The products of these genes interact with each other in vivo and in vitro (3,4), and participate in the control of intracellular trafficking, deficits in which are recognized in a wide range of neurological disorders (6).…”
mentioning
confidence: 99%
“…(Packman & Attanasio, 2004). Several research groups' recent accomplishments in the areas of neuroimaging (e.g., Beal et al, 2013;Cai et al, 2014;Chang et al, 2011;Choo et al, 2012;Sitek et al, 2016;Wymbs et al, 2013) and gene discovery (e.g., Benito-Aragón et al, 2020;Frigerio-Domingues & Drayna, 2017;Frigerio-Domingues et al, 2019;Kang et al, 2010;Raza et al, 2012) indicate substantial progress regarding the former of these two causality questions. Progress in addressing the latter question continues to lag as very few specific hypotheses have been formulated to suggest biologically plausible mechanisms that may explain the individual occurrences of sound/syllable repetitions and sound prolongations.…”
Section: Introductionmentioning
confidence: 99%
“…In this review we will only cite those genes that are present in non-syndromic stuttering. Around 9% of patients with a familiar background associates with the GNPTAB, GNPTG, and NAGPA genes [68] . The importance of these genes is based on replication in subsequent studies, confirming a key role in stuttering [69] .…”
Section: Stutteringmentioning
confidence: 99%
“…These genes may also be affected in mucolipidosis. Unlike mucolipidosis, the characteristics of the mutations found in stuttering lie in their typically heterozygous character, with nonsense mutations, a modest reduction of enzyme function and different mutation sites [68] .…”
Section: Stutteringmentioning
confidence: 99%